A Comparative Study of Centralised, Decentralised, and Hybrid Models of Quality Assurance Higher Education in Australia, Nigeria, and Indonesia - Dimara, Frits; Faidiban, Paskalina (Jurnal Akuntabilitas Manajemen Pendidikan, 2026)
The study provides both theoretical and practical contributions by offering a cross-country comparative perspective, proposing the advantages of decentralization as an alternative conceptual framework, and outlining policy implications for higher education institutions and regulators. The paper compares the quality assurance (QA) systems for higher education in Australia, Nigeria, and Indonesia and examines the effects for graduate relevance, accountability, and global competitiveness. Using the PRISMA 2020 as guidelines to conduct a Systematic Literature Review (SLR) of 40 articles, including 16 from Australia, 10 from Nigeria, and 14 from Indonesia. The outcomes indicate that, despite present institutional gaps, Nigeria uses a centralized model that emphasizes national consistency, Indonesia implements a hybrid model that combines external accreditation with internal QA, and Australia adopts an autonomy-driven model that follows risk-based regulation, supporting innovation while preserving standards. In order to promote QA in higher education, this study presents a fresh conceptual framework called the advantages of decentralization, which emphasizes the balance between accountability, flexibility, and equity. The approach focuses how academic culture, economic capability, and governance structures significantly impact QA models and outcomes. Additional bibliometric and content studies show that Australia dominates the way in QA research, with Indonesia showing consistent growth and Nigeria demonstrating that no strategy is perfect: Nigeria maintains consistent standards but may experience stagnation, while Indonesia attempts imbalances and Australia encourages innovation but run the risk of inequity.